Oxidation of Cellulose and Nanocellulose Isolated from Paraserianthes falcataria by Potassium Permanganate - Ikhtiarini, Nur; MASRURI, Masruri; Mariyah Ulfa, Siti; Widodo, Nashi (The Journal of Pure and Applied Chemistry Research, 2023)
A high crystallinity proportion of cellulose and nanocellulose in some points contribute to the solubility in polar solvent. This paper reports oxidation reaction study by using potassium permanganate of the cellulose and nanocellulose isolated from the soft wood of Paraserianthes falcataria. Â The reaction was conducted under acidic condition at 30 and 70Â°C for 12 and 24 hours. The product was characterized by FTIR, XRD, SEM, DTA-TGA, and solubility test. Oxidation of cellulose resulted in the opening of hemiacetal of glucopyranose chain, as indicated by carbonyl peak recorded in FTIR spectra. The particle size was determined and amorphous product of cellulose and nanocellulose was isolated. In addition, the DTA/TGA analysis indicate the oxidized cellulose give a more stable structure than the nanocellulose.